Digital Piezomaterial Based on Piezoceramic-Polymer Composite for Ultrasonic Transducers - D.I. Makarev; A.N. Rybyanets (Журнал нано- та електронної фізики)
Laboratory samples of digital piezomaterial with high mechanical Q-factor based on the mixed piezoceramic-polymer composite adapted for the piezoelectric elements manufacturing (by the additive technology of powder layer binding) were obtained. The material Q-factor dependence of the sound velocity ratio of the piezoceramiс and polymer was determined. It is shown that ultrasonic transducers for a number of technical applications can be made on a basis of this piezomaterial.